Effect of seasonality and estuarine waters on the phytoplankton of the Guamá River (Belém, Amazon, Brazil) - PAOLA VITORIA B. PIRES; ELIANE B. DE SOUSA; ALINE L. GOMES; CELLY JENNIFFER S. CUNHA; VANESSA B. DA COSTA TAVARES; SAMARA CRISTINA C. PINHEIRO; BRUNO S. CARNEIRO; NUNO FILIPE A.C. DE MELO (Anais da Academia Brasileira de Ciências, 2024)
Abstract This study aimed to analyze the application of the Phytoplankton Community Index-PCI and Functional Groups-FG in determining the water quality of the Guamá River (Pará, Amazônia, Brazil). Samplings occurred monthly for analyses of phytoplankton and physical and chemical parameters, for two years, at the station where water was collected for human supply consumption. Seasonality influenced electrical conductivity, total suspended solids, dissolved oxygen, transparency, winds, true color, and N-ammoniacal. The ebb tide showed high turbidity and suspended solids. The density varied seasonally with the highest values occurring in September and December (61.1 ind mL-1 and 60.2 ind mL-1, respectively). Chlorophyll-a was more elevated in December (21.0 ± 4.7 µg L-1) and chlorophyll-c higher in relation to clorophyll- b indicated the dominance of diatoms. Functional Group P prevailed in the study months. Through the PCI índex the waters of Guamá River varied from reasonable to excellent and the TSI ranged from oligo to mesotrophic. The use of Functional Groups proved to be a promising tool in the determination of water quality since it covered the most abundant species in the Environment, but the PCI is not adequate to characterize Amazonian white-waters rivers, which have diatoms as the leading dominant group.